2021
DOI: 10.3892/etm.2021.10348
|View full text |Cite
|
Sign up to set email alerts
|

Guillain‑Barré syndrome associated with Covid‑19: A close relationship or just a coincidence? (Review)

Abstract: Several neurological complications affecting the central and peripheral nervous system were described secondary to COVID-19 infection such as hyposmia, headache, nausea, impaired consciousness, psychosis, neurocognitive syndromes and even cerebrovascular accidents. The mechanism of these complications is not fully understood, but heterogenous mechanisms such as cytokine storm, secondary hypercoagulability and direct neurotropism of the virus are thought to be involved. Guillain-Barré syndrome is a heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…NCAM was found to be 85% identical to SARS-CoV-2 envelope proteins in silica, suggesting that an immune response against SARS-CoV-2 could theoretically lead to demyelination and polyneuropathy via molecular mimicry [ 36 ]. Relatively high Guillain–Barre Syndrome (GBS) incidence among COVID-19 victims would further support this conclusion, but this is not conclusively documented in COVID-19 [ 3 , 29 , 37 ]. However, we found that neither the serum levels of spike protein nor the immunoglobulin titer against it correlated to the NCAM-1 increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NCAM was found to be 85% identical to SARS-CoV-2 envelope proteins in silica, suggesting that an immune response against SARS-CoV-2 could theoretically lead to demyelination and polyneuropathy via molecular mimicry [ 36 ]. Relatively high Guillain–Barre Syndrome (GBS) incidence among COVID-19 victims would further support this conclusion, but this is not conclusively documented in COVID-19 [ 3 , 29 , 37 ]. However, we found that neither the serum levels of spike protein nor the immunoglobulin titer against it correlated to the NCAM-1 increase.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been linked to abnormalities in the central nervous system such as the loss of smell and taste, cognitive decline, delirium, cerebrovascular accidents, neuronal autoimmune illnesses, and psychiatric disorders [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, the heterogeneity of symptoms remains puzzling [ 1 , 3 , 7 , 8 , 9 , 10 ]. The development of these abnormalities often occurs within two days from the onset of symptoms [ 1 , 5 , 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…doi: https://doi.org/10.54905/disssi/v27i133/e168ms2806 people each year. Older patients and male gender appear to be more severely impacted than younger people (Stoian et al, 2021).…”
mentioning
confidence: 91%
“…These patients were also treated with immunoglobulins, as well as antiretroviral therapy and hydroxychloroquine. Ultimately, two patients died from these studies (5) (6).…”
mentioning
confidence: 99%